Enhanced recovery after surgery (ERAS) guided gynecologic/oncology surgery - The patient's perspective - Emma Sian Jenkins; Rachel Crooks; Khara Sauro; Gregg Nelson (Elsevier, 2024)
Objective: Enhanced recovery after surgery (ERAS) pathways have demonstrated improvements in outcomes following benign gynecologic and gynecologic oncology surgery. However, there is limited data reporting the benefit of ERAS from the patient's perspective. This study aimed to explore patient knowledge of and experience with ERAS-guided surgery. Methods: This interpretive descriptive study included participants who had undergone ERAS-guided gynecologic and gynecologic oncology surgery in Alberta, Canada using convenience sampling. Semi-structured interviews explored patient knowledge of ERAS, overall experience with surgery and recommended changes for surgical care. An inductive thematic analysis was conducted. Results: Eight females aged 26-76 years old participated in the study who had gynecologic (n = 4) and gynecologic oncology (n = 4) surgery. Six themes central to participant experience of ERAS-guided surgery were identified: patient expectations, individual motivation, values and support, healthcare provider communication, trust in healthcare providers, COVID-19 and care co-ordination. Overall, specific knowledge of ERAS was low. Expectations were set by previous experience of healthcare (previous surgery or occupation), as well as information provided by healthcare professionals. Participants whose expectations aligned with physical experience of ERAS provided favourable perspectives. Participants recommended improving the quality, relevance and availability of information and establishing accessible follow up strategies. Conclusion: Based on the finding that knowledge about ERAS was minimal, we advocate for improved education pertaining to ERAS recommendations. Acknowledging patients' expertise and motivation to engage in their care maybe one strategy to improve compliance with ERAS guidelines and improve outcomes for both patients and the healthcare system.